2020
DOI: 10.3390/su12083409
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation of Cultural Services in the Czech Republic via Multi-Criteria Decision Analysis

Abstract: Culture is an irreplaceable means of transferring information between generations. The development of culture, the cultural environment, and the effect of culture exist over the long term. The results are not shown immediately, whereas the economics of subjects of this area (including theatres) are subject to public control. Public control forces these entities to use public finances efficiently, economically, and effectively. A sample of 11 indicators showing techniques and financial efficiency was chosen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A question for a broader discussion is whether, regarding the social benefit and interest, the inefficiency of public galleries is less significant than the positive externalities being produced by them in the form of accessible cultural services. This is discussed by Vavrek and Bečica (2020) within the context of public theaters, and by Vrabková (2019) in relation to public libraries. Another perspective to be applied to the above-stated situation is that if positive externalities of galleries or other cultural services being supported from the public budgets cannot be exactly measured, then the most reliable indicator of their efficiency as well as the level of positive externalities is represented by the number of visitors (users) of these cultural services.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A question for a broader discussion is whether, regarding the social benefit and interest, the inefficiency of public galleries is less significant than the positive externalities being produced by them in the form of accessible cultural services. This is discussed by Vavrek and Bečica (2020) within the context of public theaters, and by Vrabková (2019) in relation to public libraries. Another perspective to be applied to the above-stated situation is that if positive externalities of galleries or other cultural services being supported from the public budgets cannot be exactly measured, then the most reliable indicator of their efficiency as well as the level of positive externalities is represented by the number of visitors (users) of these cultural services.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another study was performed on the dimensions of cultural environment and development. To evaluate the Czech theatres' economy, Vavrek and Bečica [31] selected 11 criteria related to financial and technical efficiency. Three objective weighting methods, including Coefficient of Variation, Standard Deviation, and Mean Weight (Equal Weights) methods, were applied to determine the selected criteria' importance and the variation coefficient indicated that financial criteria are more significant than technical criteria, but standard deviation gave importance to technical criteria.…”
Section: Recent Studies On Objective Weighting Methodsmentioning
confidence: 99%
“…variants that can be real but fictitious as well), and the longest distance to a negative ideal solution. This method is tackled more deeply in Shih, Shyur & Lee ( 2007), Seyedmohammadi and colleagues (2018), Vavrek and Bečica (2020a), and is calculated as follows.…”
Section: Topsis As a Methods Of Multi-criteria Evaluationmentioning
confidence: 99%